A Narrative Review of Pharmacy-Led Antimicrobial Stewardship Integrated with Radiology and Lab Diagnostics for Epidemiological Tracking of Hospital-Acquired Infections under Health Administration Oversight - Almarshood, Hamad Salim Hamad; Mohammed Ali Alharbi; Yahya Saeed Ali Al Qahtani; Ayed Mohammed Sror Alhisham; Sharifah Gamea Almutairy; Hameed Ahmd Al Kharmani; Saud Abdullah Al-Mousa; Mosalam Saed Alattaf (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Hospital-acquired infections (HAIs) and antimicrobial resistance (AMR) represent critical threats to global health security, straining healthcare systems and worsening patient outcomes. Traditional antimicrobial stewardship (AMS) programs, while essential, often operate in clinical silos, lacking integration with key diagnostic and epidemiological data streams. This fragmentation impedes timely, targeted interventions and holistic infection control. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review aims to synthesize current evidence on the impact, implementation strategies, and outcomes of integrating pharmacy-led AMS with radiology and laboratory diagnostic data under coordinated health administration oversight, specifically for the epidemiological tracking and management of HAIs. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive literature search was conducted across PubMed, Scopus, and Web of Science for studies published between 2010 and 2024, focusing on interdisciplinary AMS models, diagnostic stewardship, and HAI surveillance. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The synthesized evidence demonstrates that integrated models significantly enhance early HAI detection, optimize antimicrobial use, and improve patient outcomes by leveraging real-time data analytics and interdisciplinary collaboration. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A synergistic, administratively supported model that unites pharmacy expertise, advanced diagnostics, and epidemiological tracking is paramount for a proactive, data-driven defense against HAIs and AMR.